Fly Ash as an Amendment Agent for Soil Fertility - Jala, Sudha (My University, 2007)
Coal is an exhaustible energy source, which plays a critical role in meeting the everincreasing energy demands of countries around the world. Combustion of coal in thermal power stations produces a variety of residues viz. fly ash, bottom ash, flue gas desulfurization waste (scrubber sludge) and fluidized bed boiler waste and coal gasification ash. The physical, chemical and mineralogical characteristics of fly ash depend on a variety of factors such as composition of parent coal, combustion conditions, the efficiency and type of emission control devices and the disposal methods used. Fly ash is an amorphous mixture of ferroaluminosilicate minerals generated from combustion of ground or powdered coal at temperature ranging from 400-1500ºC. It is composed predominantly of small, glassy, hollow particles with specific gravities ranging from 2.1 to 2.6. g cm-3. Physically, fly ash occurs as very fine particles having an average diameter of <10 mm, low to medium bulk density, high surface area and light texture which are aggregated into micron and sub-micron spherical particles, of size ranging from 0.01 to 100 mm, with smaller particles entrapped within large spheres. 90-99% of fly ash consists of Si, Al, Fe, Ca, Mg, Na and K. Major matrix elements in fly ash are Si and Al together with significant percentage of K, Fe, Ca and Mg. Fly ash contains all naturally occurring elements and is substantially rich in trace elements like lanthanum, terbium, mercury, cobalt and chromium. Over 225 million tonnes of coal is being produced annually in India. The coal, which is of poor quality, generates on an average about 40% ash. In India over 100 thermal power stations are producing around 108 million tonnes of fly ash every year and it is expected to double by the year 2010. On account of its heterogenous nature fly ash has the potential to be used as a soil-ameliorating agent in agriculture and forestry. Field and greenhouse studies both indicate that many chemical constituents of fly ash may benefit plant growth and can improve agronomic properties of soil. Fly ash addition alters physical properties of soil such as texture, bulk density, water holding capacity and particle size distribution.
Keywords: amendment agent; Fly ash; Soil Microorganisms; Acacia Auriculiformis